Establishment of Historical Control Data on Rats and Mice for Preclinical Studies - Venkatesan, P.S.; S.Sundaresan; M.Eswarya; S.Sowmiya; M.Madhavaselvi (The Indian Veterinary Journal, 2026)
Toxicology studies and other biomedical research can only be interpreted when adequate reference ranges established from healthy control animals are available. Each animal species being evaluated requires a unique set of reference values for various hematology and biochemical parameters. The stock animals were selected from Mass Biotech, Chengalpet, Tamil Nadu, India, during the years 2019 to 2023. The selected animals were found to be healthy under veterinary examination. Wistar rats (Rattus norvegicus) and Swiss albino mice (Mus musculus) were selected from the age group of 5-12 weeks. Heamatology, biochemistry, feed consumption and body weight were estimated and mean reference range was tabulated with standard deviation. The mean SGPT value of male rat was 70.16; the female rat was 41.14. The mean SGOT value of the male rat was 124.49, and that of the female rat was 95.3. The mean SGPT value of female mice was 31.14, and that of male mice was 46.72. The mean SGOT was 64.31 in female mice and 170.83 in male mice. The mean ALP value of female mice is 147.7. The mean haemoglobin value of male mice is 9.22, and the mean RBC and WBC count is 3.30 and 6.39, respectively. Other hematology and biochemical parameters of both sexes were estimated. The estimated variations in each parameter, with wider ranges, might be due to animal sources, geographical variations in terms of environment and genetic factors. So, the estimated values could be comparable with the data generated in similar geographical regions.